2008
DOI: 10.1109/tnet.2007.902687
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Per-Flow Throughput and Capturing Starvation in CSMA Multi-Hop Wireless Networks

Abstract: Abstract-Multi-hop wireless networks employing random access protocols have been shown to incur large discrepancies in the throughputs achieved by the flows sharing the network. Indeed, flow throughputs can span orders of magnitude from near starvation to many times greater than the mean. In this paper, we address the foundations of this disparity. We show that the fundamental cause is not merely differences in the number of contending neighbors, but a generic coordination problem of CSMA-based random access i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
208
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(212 citation statements)
references
References 26 publications
4
208
0
Order By: Relevance
“…Canceling the remaining terms we get (8), so π PH indeed satisfies (12). Substituting π PH into (13), and canceling common terms yields…”
Section: Proof Lemmamentioning
confidence: 96%
“…Canceling the remaining terms we get (8), so π PH indeed satisfies (12). Substituting π PH into (13), and canceling common terms yields…”
Section: Proof Lemmamentioning
confidence: 96%
“…Many studies have already identified the channel unfair share and the flow starvation problem in 802.11-based wireless ad hoc networks [37,13,16,20]. There have also been numerous efforts to mitigate the inter-cell interference problem, including channel assignment [17,28,34], power control (or carrier sense control) [8,26,36], and association control [9,10].…”
Section: Related Workmentioning
confidence: 99%
“…In particular, it has been shown that both EDCA and DCF do not utilize their maximum potential capacity, and their throughput performance and degree of fairness degrade significantly as the number of contending stations increases [21]. A more general problem with EDCA is that it inherently involves the unfairness problem stemming from the CSMA-based medium access rule [23,16].…”
Section: Ieee 80211e: the Current Qos Support Mechanismmentioning
confidence: 99%
See 2 more Smart Citations